Formulasi dan Uji Aktivitas Antibakteri Sediaan Sabun Cair Ekstrak Etanol Daun Kopi Arabika (Coffea arabica L.) Terhadap Bakteri Staphylococcus aureus - Amaliana, Amaliana; Nasution, Haris Munandar; Lubis, Minda Sari; Rahayu, Yayuk Putri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Coffee leaves (Coffea arabica L.) are a part of the coffee plant that is not widely used. Coffee leaves contain flavonoids, alkaloids, saponins, caffeine and polyphenols. Coffee leaves are a natural ingredient that has antibacterial and antioxidant activity, so they need to be used. develop it into pharmaceutical preparations to increase ease of use, one of which is liquid soap preparations The aim of this research was to determine the secondary metabolite content of simplicia powder and ethanol extract of coffee leaves, formulate ethanol extract of coffee leaves into liquid soap, determine the physical quality of the preparation and test the activity against Staphylococcus aureus bacteria. The method used in this research is to make a liquid soap formulation from Arabica coffee leaves and test its effectiveness as an antibacterial against Staphylococcus aureus bacteria. This research was carried out experimentally with the independent variable being the concentration of Arabica coffee leaf ethanol extract: F1 contains 2.5 grams of active substance, F2 contains 5.0 grams of active substance, F3 contains 7.5 grams of active substance, dependent variable: leaf simplicia phytochemical screening test Arabica coffee, antibacterial activity test against Staphylococcus aureus bacteria. Quality of liquid soap preparations from ethanol extract of Arabica coffee leaves using stability tests (pH of the preparation, homogeneity, viscosity and height of foam) and antibacterial tests using the agar diffusion method (well method). The research results show that simplicia powder and ethanol extract of coffee leaves contain alkaloid, flavonoid, tannin and saponin chemical compounds. The organoleptic test results of liquid soap have a distinctive smell, a combination of coffee and rose leaves, are blackish brown in color, and are in the form of a thick liquid. The stability test results of all formulas are stable. The pH test ranges from 9.05 to 9.43. Test foam height 35- 40 mm. The viscosity test results ranged from 735.0-894.8 cpoise, antibacterial activity had an k- (Blanko) concentration inhibition zone of 13,6 mm FI concentration liquid soap obtained a result of 15.7 mm, FII concentration liquid soap obtained a result of 18.4 mm, FIII concentration liquid soap obtained a result of 18.75 mm compared to the control positive obtained a result of 18.8 mm.